2016
DOI: 10.4315/0362-028x.jfp-15-322
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of Ingoing Sodium Nitrite, Sodium Ascorbate, and Residual Nitrite Concentrations on Growth Parameters of Listeria monocytogenes in Cooked, Cured Pork Sausage

Abstract: Sodium nitrite has been identified as a key antimicrobial ingredient to control pathogens in ready-to-eat (RTE) meat and poultry products, including Listeria monocytogenes. This study was designed to more clearly elucidate the relationship between chemical factors (ingoing nitrite, ascorbate, and residual nitrite) and L. monocytogenes growth in RTE meats. Treatments of cooked, cured pork sausage (65% moisture, 1.8% salt, pH 6.6, and water activity 0.98) were based on response surface methodology with ingoing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 33 publications
3
6
0
1
Order By: Relevance
“…On the other hand, no effect was observed in the BIX broth. This study confirmed that ingoing nitrite concentration influences L. monocytogenes growth as observed previously (KING et al 2016), but single bixin potassium salt is not able to inhibit pathogen growth. The results show how the use of bixin could allow a reduction in the use of nitrite.…”
Section: Microbiological Analysissupporting
confidence: 91%
“…On the other hand, no effect was observed in the BIX broth. This study confirmed that ingoing nitrite concentration influences L. monocytogenes growth as observed previously (KING et al 2016), but single bixin potassium salt is not able to inhibit pathogen growth. The results show how the use of bixin could allow a reduction in the use of nitrite.…”
Section: Microbiological Analysissupporting
confidence: 91%
“…Moreover, it should be noted that the presence of sodium ascorbate (0.3 g/kg) in the different recipes (Ni-120, Ni-90) may have enhanced the anti listerial effect of sodium nitrite as previously described by others. [15,48] Among the three alternative products that were tested as nitrite salt replacement, the vegetable stock (VS) gave, for almost all the parameters tested, results that were very close to those of Ni-120, whatever the dose of the food additive. Indeed, results on luminal lipid peroxidation and ATNC formation with different concentrations of vegetable stock are similar to nitrites doses of 120, (Figure 6A-B), 80 or 40 mg/kg (Figure S1A-B).…”
Section: Discussionmentioning
confidence: 98%
“…The present study showed that sodium nitrite added in the cooked ham products exerted an inhibitory effect against L. monocytogenes, as previously reported on various ready-to-eat cooked meat products. [15][16][17]48] Although sodium nitrite alone was not sufficient to prevent the growth of L. monocytogenes during actual shelf life of sliced cooked ham products, ingoing amounts of sodium nitrite equal or greater than 90 mg NaNO2 / kg led to a significant reduction of L. monocytogenes growth during the first 3 weeks of storage compared to the control without nitrite (Ni-0). Moreover, it should be noted that the presence of sodium ascorbate (0.3 g/kg) in the different recipes (Ni-120, Ni-90) may have enhanced the anti listerial effect of sodium nitrite as previously described by others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although nitrates/nitrites inhibit the growth of Clostridium botulinum spores (Lebrun et al., 2020), other research studies have demonstrated that maximum acceptance levels in foods allowed by law are not enough to inhibit the growth of concern foodborne pathogens such as Listeria monocytogenes , Bacillus cereus , Staphylococcus aureus , Clostridium perfringens or Pseudomonas spp. (Cenci‐Goga et al., 2014; Grispoldi et al., 2019; Hospital et al., 2017; King et al., 2016; Rossi et al., 2016). The characteristic reddish color of meat products made with nitrates/nitrites is caused by myoglobin, an iron and oxygen‐binding protein found in skeletal muscles (Suman et al., 2016).…”
Section: Introductionmentioning
confidence: 99%